Impact of inflammatory bowel disease on quality of life, anxiety, and depression: a multicenter study in Lima, Peru - Paredes-Méndez, Juan Eloy (2026)
Inflammatory bowel disease (IBD) is a chronic condition characterized by periods of activity and remission, with an uncertain and unpredictable course. It mainly affects the economically active population and may compromise physical, psychological, social, and occupational well-being. Objective: The aim of this study was to describe health-related quality of life and the presence of anxiety and depression in patients with IBD. Materials and methods: An observational, descriptive, cross-sectional study was conducted between April and December 2023. Patients older than 16 years with a confirmed diagnosis of IBD, at least six months of disease duration, and regular pharmacological treatment were included. The Inflammatory Bowel Disease Questionnaire-32 (IBDQ-32), the Patient Health Questionnaire-9 (PHQ-9), and the Generalized Anxiety Disorder-7 (GAD-7) were administered. Results: Most patients (70%) reported a high quality of life, with no significant differences between ulcerative colitis and Crohn’s disease. However, a significant reduction in health-related quality of life was observed in patients with active disease. Symptoms of depression were identified in 62.2% of patients, and anxiety in 58.1%, with both conditions being more frequent in patients younger than 30 years. Conclusions: Although most patients with IBD maintain a good quality of life, more than half experience symptoms of anxiety or depression, even during clinical remission. These findings highlight the importance of integrating mental health assessment and management as an essential component of comprehensive IBD care, in accordance with STRIDE II recommendations.